After the crime: the power of restorative justice dialogues between victims and violent offenders - Miller, Susan L. (New York University Press, 2011)
Tossing turkeys and other stories : what do they say about crime and punishment? -- Getting personal : the power of storytelling -- Donna and Jamel : living in different prisons -- Allison and James : from horror to gratitude -- Laurie and Paul : emerging from a cocoon -- Melissa and Steven : losing innocence -- Scott and Bruce : thou shalt not-- -- Leigh and Jenny : lives interrupted -- Julie and Kevin : in memoriam -- Kathleen and Wayne : a mother's love -- Chris and Brett : misguided chivalry -- The importance of storytelling for restorative justice